Grief Journey in Bill Clegg's Novel Did You Ever Have a Family (2015) - Khairin Maranda; Delvi Wahyuni (English Language and Literature, 2019)
This thesis is a psychoanalysis reading of a novel which is written by Bill Clegg entitled Did You Ever Have a Family (2015). It explores the issue of grief journey which is experienced by main character before she is managed to heal from her grief. The analysis of grief journey is used the concept of Elisabeth Kubler Ross (1969) of five stages of grief. It is also intended to find out the contribution of multiple narrators in revealing the issue of grief journey. The result of this analysis shows the depiction of main character’s grief journey from multiple characters’ perspective.